Rapid caldera subsidence and fluctuating eruption dynamics: the lithostratigraphy and structure of the Loch Bà Caldera, Isle of Mull, NW Scotland - Nicholls, Peter; Brown, David; Dymock, Ross (Volcanica, 2024)
Caldera-forming eruptions represent extremely hazardous events. The Loch Bà Caldera on the Isle of Mull, NW Scotland, preserves an 120 m thick sequence of Palaeogene silicic pyroclastic rocks and collapse breccias. Here we present the first detailed account of the lithostratigraphy and architecture of the caldera-fill. A silicic explosive eruption generated pyroclastic density currents that deposited a range of rhyolitic ignimbrite lithofacies as the caldera collapsed. Abrupt changes in ignimbrite lithofacies and lateral thickness changes are attributed to volcano-tectonic faults and incremental collapse of the caldera. Five eruption phases have been recognised that record rapid switching between sustained high-fountaining and low-fountaining “boil-over” eruptions. The ignimbrites are unconformably overlain by mesobreccias and inward rotated megablocks of basalt lava country rock, which record catastrophic inward collapse of the caldera walls and margins. Our results provide new insights into caldera collapse and intra-caldera-fill that can be applied to other volcanoes worldwide.